KEMELIMPAHAN IKAN AIR TAWAR DI DESA SUNGAI BAKAR KECAMATAN BAJUIN KABUPATEN TANAH LAUT - Almira Ulimaz (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2020)
Tanah Laut District is a district that brings together mountain highlands with lowlying sea waters within a province in South Kalimantan. It makes the area that is rich in biological natural resources in the form of agricultural products and livestock products such as fish. This natural resource supported by its natural geographical conditions, such as the presence of sea and river in one area. Rivers in this region have biological richness in the form of freshwater fish. Therefore, a study conducted which aimed to describe the abundance of freshwater fish species in Sungai Bakar Village, Bajuin Sub-District, Tanah Laut District. The method used in this research is a descriptive method that is describing the results of research with observation techniques in the form of direct visits to the field. The study area divided into three zones, namely shallow, medium, and deep, with each region consisting of 10 points, collecting samples using a net and fishing line with repetition three times. Data analysis carried out qualitatively and quantitatively. The results showed that the highest or largest fish abundance was Anabas testudineus in zone A (shallow) 39.18%, zone B (medium) 48.92%, and zone C (deep) 42.59%. The lowest fish abundance was zone A (shallow) Clarias batrachus 8.20%, zone B Clarias batrachus (medium) 7.8%, and zone C Oreochromis niloticus, Barbodes gonionotus, and Macrones gulio (deep), with both same abundances at 17.13%.